Employee Well-Being Dynamics and the Wise Leadership Model in the Digital Industry - Umi Zunaidah; Ferdi Antonio; Rasty Yulia; Akhmad Baidun; Fransiska Husain (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The purpose of this study is to analyze employee well-being dynamics and the wise leadership model in the digital industry. This research approach uses a qualitative approach. The data used are secondary data. Data analysis uses causal relationship analysis. The research results show that in the fast-paced digital industry, employee well-being dynamics are no longer a supplementary program to human resources development, but rather a core business strategy. Mentally and physically healthy employees are the driving force of innovation. The wise leadership model is a bridge that connects the demands of the speed of the digital world with the natural human need for security, appreciation, and meaning. When leaders are able to use their wisdom to put humans above algorithms, digital organizations will not only survive but also thrive.